Evaluation of Physical and Mechanical Properties of Coating Mortar with Partial Replacement of Sand by Blast Furnace Flue Dust - Manoela da Silva Carvalho; Vinicius Lima de Arruda; Leonardo Simoni; Felipe Fernandes de Oliveira; Robson Fleming (Cerâmica)
Abstract This study evaluates the potential partial replacement of sand by blast furnace flue dust (BFFD) in coating mortars to reduce the environmental impact caused by solid residues generated by the iron-making industry. Mortars were produced with varying rates of sand replacement by BFFD, and curing was conducted at room temperature and in lime-saturated water. Axial and radial compressive strength were evaluated at ages up to 28 days, and density, water absorption, and apparent porosity were measured after 28 days of curing. The results indicate that partial replacement of sand by BFFD is viable after curing at ambient conditions, leading to a reduction in mortar density without significantly altering compressive strength. However, the compressive strength of BFFD-added mortars decreases when curing is carried out in water-saturated lime.